Haemogregarina daviesensis sp. nov. (Apicomplexa: Haemogregarinidae) from South American lungfish Lepidosiren paradoxa (Sarcopterygii: Lepidosirenidae) in the eastern Amazon region - Esteves-Silva, Pedro Hugo; Lucas da Silva, Maria Regina [UNESP]; O'Dwyer, Lucia Helena [UNESP]; Tavares-Dias, Marcos; Viana, Lucio Andre (Springer, 2019)
Based on morphology and morphometry of gametocytes in blood and molecular phylogenetic analysis, we described a new species of hemoparasite from the genus Haemogregarina isolated from Lepidosiren paradoxa in the eastern Amazon region. Haemogregarina daviesensis sp. nov. is characterized by monomorphic gametocytes of varying maturity stage and their dimensions were 16 +/- 0.12 mu m (range 13-18) in length and 6 +/- 0.97 mu m (range 5-8) in width. The morphological and morphometric data were not identical with other haemogregarine species from fish. All specimens of L. paradoxa analyzed were infected by H. daviesensis sp. nov. and the parasitemia level was moderate (1-28/2000 blood erythrocytes). Two sequences were obtained from L. paradoxa, and these constituted a monophyletic sister clade to the Haemogregarina species. In addition, H. daviesensis sp. nov. detected here grouped with Haemogregarina sp. sequences isolated from chelonian Macrochelys temminckii, with 99% bootstrap support. This study provides the first data on the molecular phylogeny of an intraerythrocytic haemogregarine of freshwater fish and highlights the importance of obtaining additional information on aspects of the general biology of these hemoparasites in fish populations, in order to achieve correct taxonomic classification.
Keywords: Haemogregarine; Lungfish; Morphology; 18S rRNA gene; Hemoparasites